Which typical floor movements of men`s artistic gymnastics result in the most extreme lumbar lordosis and ground reaction forces? - Eyssartier, C.; Robert, M.; Billard, P.; Thoreux, P.; Sauret, C. (Sports Biomechanics, 2022)
Back pain is prevalent among gymnast populations and extreme flexion or extension of the lumbar spine along with high ground reaction forces (GRFs) are known to increase intervertebral stress. The aim of this study was to determine which postures and dynamic conditions among common floor movements provide the greatest risk of injury in men`s artistic gymnastics (MAG). For this purpose, lumbar spine curvatures, obtained through a full-body subject-specific kinematic model fed by motion capture data, and GRFs on feet and hands were compared between typical floor movements of MAG (pike jump, round off back handspring, front handspring, forward and backward tucked somersaults) performed by six adolescent gymnasts. The round off back handspring and the pike jump resulted respectively in the largest lumbar extension and flexion, and the forward tucked somersault take-off in the highest GRF. At ground impacts, the largest lumbar flexion was during the backward tucked somersault landing and only the back handspring hands ground contact phase led to lumbar extension. Such identification of high-risk conditions should enable better back pain management in gymnastics through more tailored training adaptations, particularly in case of pathologies or musculoskeletal specificities.